2006
DOI: 10.1007/s10895-006-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Poly(Sodium N-Undecanoyl-l-Leucylvalinate), Poly(Sodium N-Undecanoyl-l-Leucinate) and Poly(Sodium N-Undecanoyl-l-Valinate) Surfactants as Chiral Selectors for Determination of Enantiomeric Composition of Samples by Multivariate Regression Modeling of Fluorescence Spectral Data

Abstract: Steady-state fluorescence spectroscopy was employed to investigate the use of chiral polymeric surfactants as chiral selectors in chiral analysis by multivariate regression modeling of spectral data. Partial-least-squares regression modeling (PLS-1) was used to correlate changes in the fluorescence spectral data of 1,1'-bi-2-naphthol (BOH), 1,1'-binaphthyl-2,2'-diamine (BNA), or 2,2,2-trifluoroanthrylethanol (TFA) in the presence of poly(sodium N-undecanoyl-L-leucylvalinate), poly(sodium N-undecanoyl-L-leucina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A recent study in our laboratory has demonstrated the utility of molecular micelles as chiral selectors for determining the enantiomeric composition of three highly hydrophobic fluorescent chiral molecules using steady-state fluorescence spectroscopy and multivariate regression analysis of spectral changes in chiral guest-host complexes [26]. In this study, differences in analyte fluorescence emission were observed due to the formation of diastereomeric complexes between the chiral molecular micelle and chiral analyte.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…A recent study in our laboratory has demonstrated the utility of molecular micelles as chiral selectors for determining the enantiomeric composition of three highly hydrophobic fluorescent chiral molecules using steady-state fluorescence spectroscopy and multivariate regression analysis of spectral changes in chiral guest-host complexes [26]. In this study, differences in analyte fluorescence emission were observed due to the formation of diastereomeric complexes between the chiral molecular micelle and chiral analyte.…”
Section: Introductionmentioning
confidence: 73%
“…We have previously reported that the extent of spectral variation will determine the prediction accuracy for enantiomeric composition [26]. Serine had the highest RMS%RE value and the lowest degree of spectral variation.…”
Section: Determination Of Enantiomeric Compositionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies in our laboratory with nonfluorescent molecular micelles confirmed that the ability of the calibration model to accurately predict the enantiomeric composition of future samples depends on the extent of the spectral variation. 11 All analytes have the same total concentration (1.0 3 10 25 M), but different emission spectra with varying enantiomeric compositions in the presence of poly-L-SUF. Table 1 shows the compositions of 12 solutions prepared for the calibration of all eight analytes.…”
Section: Determination Of Enantiomeric Composition Using Optimized Comentioning
confidence: 99%
“…Various chiral selectors, such as cyclodextrins, molecular micelles, antibody, and crown ethers have been widely used because of their chiral recognition abilities. [21][22][23][24] However, the use of many current chiral selectors is often limited because of low solubility, difficult organic syntheses, instability at high temperature, as well as high cost. In addition, many currently available chiral selectors require the use of another solvent and sometimes more than one solvent system if the analyte and the chiral selector are not soluble in the same solvent.…”
Section: Introductionmentioning
confidence: 99%